Application of a transmission line model to evaluate the influence of structural defects on the corrosion behavior of arc-PVD CrN coatings. Issue 15 (1st August 2021) - Cedeño-Vente, M.L.; Manríquez, J.; Mondragón-Rodríguez, G.C.; Camacho, N.; Gómez-Ovalle, A.E.; Gonzalez-Carmona, J.M.; Alvarado-Orozco, J.M.; Espinosa-Arbelaez, D.G.
Abstract: The effect of bias voltages (40 V, 80 V, and 40/60/80 V) on microstructure and electrochemical properties of arc-PVD CrN coatings were evaluated. Increasing the bias voltage produced microstructural changes, from well-defined columns to columnar grains, and increased defect size. The electrochemical response proved susceptible to the defect type. Nano-droplets promoted the formation of oxides, while large pores allowed the migration of the electrolyte to the substrate/CrN interface. An impedance equivalent circuit based on the Bisquert transmission line was proposed to fit the experimentally obtained impedance spectra. The equivalent circuit allowed correlating the coating electrochemical response to the defect densities and sizes. Samples deposited with 40 V showed the lowest corrosion current (0.05 μA/cm 2 ± 0.01), which was supported by the highest resistances to the transport of ions through the pores ( R p = 1047 ± 88 kΩꞏcm 2 ). Films obtained with 80 V reduced R p values by two magnitude orders compared to CrN 40 V. The increase of pore resistance in CrN 40 V was associated with the oxidation of nano-droplets (proposed auto-protection phenomenon), which blocks open pinholes due to the smallest average size of defects. Tailoring a gradual increase of the bias voltage (40/60/80 V) preserves the auto-protection mechanism of droplets and improves the surface finish of the coating.